EFFECT OF WATER-SOLUBLE OMEGA-3 PREPARATION ON CARDIOVASCULAR AND RESPIRATORY SYSTEM PARAMETERS - Raksha-Sliusareva, O.A.; Boіeva S.S.; Sliusarev, O.A.; Chernyshova, O.Y.; Voloshyna, O.V.; Kovalenko, P.G.; Potapov, U.O. (World of Medicine and Biology, 2024)
The impact of a new water-soluble Omega-3 drug on the functional state of the cardiovascular and respiratory systems was determined using the example of residents of the ecologically disadvantaged Donetsk region (Mariupol) during military operations (conducting the Joint Forces Operation). The study was conducted on 131 healthy female volunteers aged 18 to 30 who did not have bad habits. Volunteers were divided into 2 groups. 68 people of the main group received a water-soluble Omega-3 drug in addition to their diet for 3 months. 63 persons in the control group did not take the drug. Before and after the Omega-3 course, the condition of the cardiovascular and respiratory systems was determined in the control subjects and main groups using functional tests: Ruffier, Serkin, Stange, Genchi, and active orthostatic test. The research established that the initial indices of the heart and respiratory system state, both in the control and main groups, did not correspond to the norm. After the water-soluble Omega-3 preparation, the results of functional tests in the subjects of the main group indicated recovery or a significant tendency to recover to the normal level of the function of the cardiovascular and respiratory systems.